A Method to Control Curcumin Release from PELA Fibers by Heat Treatment. Issue 3 (1st June 2016) - Chen, Weiming; EI‐Hamshary, Hany; Al‐Deyab, Salem S.; Mo, Xiumei
Abstract: Poly(ethylene glycol ‐co‐ DL‐lactide) (PELA) is a biodegradable polymer, which has attracted considerable interest in the area of drug release due to its potential as drug carrier. Drug‐loaded electrospun PELA fibers tend to be a promising candidate for local chemotherapy application in the future. In this study, curcumin was encapsulated into PELA fibers (Cur@PELA) for drug delivery via electrospinning. It was found that the shrinkage ratio, porosity, water absorption and water contact angle of Cur@PELA fiber membrane could be changed by heat treatment with different heating temperature (45°C, 50°C) and heating time (5 min, 10 min, 20 min). Moreover, the release rate of curcumin from Cur@PELA fibers was influenced by the porosity, water absorption and water contact angle of the drug‐loaded membrane. Heat treatment is thought to be a novel method to control release of drug from electrospun PELA fibers.